Proust Between Deleuze and Derrida The Remains of Literature - Dutton, James (Crosscurrents : CROSS, 2022)
Explores the deep affinity between Proust's textual experimentation and the revolutionary philosophical interventions of Derrida and DeleuzeReads Proust's relevance to continental philosophy and influence on its literariness Emphasises important, but significantly ignored Derridean and Deleuzean (and Deleuzo-Guattarian) concepts and key terms, like restance, the sumplokē, differentiation, the noēteon and the black hole/white wall systemFollows À la recherche du temps perdu through its 'affective arc', and uses desire, love, jealousy and grief to draw out new perspectives from the work of Derrida and DeleuzeJames Dutton argues that Proust's lone published text, À la recherche du temps perdu (1913-27), stages a uniquely productive encounter between philosophy and literature. In its genre-defying originality, it anticipates some of the most important concepts and strategies of poststructuralist French thought exemplified in the work of Jacques Derrida and Gilles Deleuze.While Derrida and Deleuze are often held to occupy irreconcilable philosophical positions, both philosophers are equally relevant to an understanding of Proust's philosophical significance, which fundamentally rests on his deferral of textual presence. Drawing on a range of conceptual tools from these two philosophers, including many that are often overlooked by commentators, Dutton shows that À la recherche stages a process of uninterrupted textual becoming, in which the distinction between the concepts of 'life' and 'literature' themselves is broken down. He reads textuality as constitutively unfinished, suggesting a new confluence between all three thinkers' emphasis on life as an endlessly productive deferral